Chemistry for engineering students: A key factor for social and technological development - Juan Antonio Llorens Molina; Gabriel Pinto (OmniaScience, 2014)
The peculiarity of Chemistry as a basic subject in Engineering Studies and its embedded potential difficulties are matters which are now common to universities worldwide. In particular, the learning of Chemistry in the new (post Bologna) degrees of Engineering in Spain and other countries is facing several challenges. In other words, there is a need to deepen into research and innovation tasks aiming at improving such studies within this new educational paradigm. Not to mention, two crucial aspects which are very often neglected, namely, reaching maximum efficiency of all types of available resources and obtaining a "knock on effect" from students and teachers at Secondary school level. The latter playing a crucial role so as to increase students' awareness of the importance that Chemistry has at this particular educational level. Not to mention, how this increases their motivation towards this subject in the Higher Education scenario.